Media Online Sebagai Strategi Pembelajaran Bahasa Arab Pada Masa Pandemi Covid-19 - Raharjo, Hermanto (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
Arabic is one of the lessons taught in several educational institutions in Indonesia. Since the covid-19 pandemic has hit the whole world, according to the policy issued by the government, all activities are carried out at home, including in the learning process. This study aims to find out some strategies that can be applied in the learning process during the covid-19 pandemic. One of them is by utilizing online media. The research approach used in this research is qualitative approach. The type of research is Research Library Research. And this research uses descriptive qualitative analysis. And this research uses descriptive qualitative analysis. From the results of the study, it can be concluded that there are several online media that can be used during the covid-19 pandemic. Among them are through whatsup application, google met, e-learning, and zoom.